Shale gas : exploration and environmental and economic impacts - Dayal, Anurodh Mohan; Mani, Devleena (Elsevier, 2017)
"'Shale Gas: Exploration and Environmental and Economic Impacts explores the shale gas exploration and production activities that are increasing globally, also presenting a basic understanding on the geological, geochemical, and geophysical aspects. The book is a key reference that is useful for researchers, the oil and gas industry, and policymakers in gas producing and prospective countries. Users will find chapters on hydraulic fracturing and shale gas drilling, as well as the environmental and economic impacts of these activities. Further chapters include case studies on the shale gas revolution in the United States and other producing countries around the world. Provides wide-ranging coverage of both the environmental and economic impacts of shale gas exploration Includes case studies that describe the prolific and potential shale gas systems from both producing and prospective countries Appeals to both those in academia and those in the unconventional gas exploration industry."--ProQuest Ebook Central website.